Prevalence of Human T-Cell Lymphotropic Virus Type 1 and Chemosensitivity of Leukaemia and Lymphoma Cells in Adult Patients in Malaysia - Selvarajan, Viknesvaran (2007)
The elucidation of virus-cancer associations is of particular importance since large numbers of people are potentially exposed to cancer. The first link relates to the causation of adult T-cell leukaemia/lymphoma (ATL), a highly malignant haematological malignancy of mature activated T cells with a poor prognosis, by a retrovirus called human T-cell lymphotropic virus type-1 (HTLV-1). The HTLV-1 tax oncoprotein plays an integral role in productive viral replication and disease progression. Seroprevalence studies demonstrated that the distribution of HTLV-1 is heterogeneous worldwide and not specific to a particular region only. Patients with this disease have a very poor prognosis because of intrinsic chemoresistance and severe immunosuppression. Hence, the general objective of the present study is to establish the prevalence of HTLV infections in leukaemia and lymphoma adult patients. The experimental design consists of two folds: screening for the presence of HTLV-1 tax gene and chemosensitivity profiles of patient cells treated with clinical chemotherapeutic agents. A total of 140 subjects consisted of lymphoid leukaemia (12%), myeloid leukaemia (26%) and lymphoma patients (62%) were included in this study. First line screening was performed using ELISA and PCR was used to detect HTLV-1 tax gene followed by confirmation using direct DNA sequencing. Mononuclear cells were isolated using density gradient centrifugation from bone marrow or peripheral blood samples of adult patients admitted to Universiti Malaya Medical Centre (UMMC), Ward 6TD. Patient cells were treated based on standard chemotherapeutic regimen for 96 hours and assessed using 3-(4, 5- dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide (MTT) cytotoxicity assay. Initial ELISA screening showed 9 samples were initially reactive and 7 patients were classified indeterminate due to inconsistency of immunoassay replicates. Further confirmation by PCR validated all seropositive patients and only four of the indeterminate samples, which yields a prevalence of 9.29% in 140 adult patients. Concurrently, the HTLV-1 tax positive patient’s chemosensitivity profiles were compared with the seronegative samples. However, a distinct relationship between the presence of HTLV-1 tax gene and chemosensitivity between these groups were not obtained. This preliminary study provided a baseline data on the prevalence of HTLV-1 infections in leukaemia and lymphoma adult patients. However, the lack of direct association of HTLV-1 tax gene with the chemotherapy resistance was mainly due to the limited sample size used in this study. Further studies should be performed in a larger cohort of patients and healthy subjects to further substantiate the preliminary data.